2016
DOI: 10.1155/2016/7178105
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Antioxidant Activities of Salvia fruticosa: An HPLC Determination of Phenolic Contents

Abstract: Objectives. Salvia fruticosa Mill. (S. fruticosa) is widely used in folk medicine. Accordingly, the present study was designed to evaluate the antioxidant and anti-inflammatory activities of S. fruticosa, and to determine the phenolic constituents of its extracts. Methods. The antioxidant activity was determined using 2,2-diphenylpicrylhydrazyl assay. Total phenolic contents were estimated using Folin-Ciocalteu reagent, and high-performance liquid chromatography was performed to identify phenolic constituents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 19 publications
5
39
1
2
Order By: Relevance
“…Up until now, different Salvia species have been investigated for their biological activity including anti-inflammatory [12], antioxidant-antifungal [13], anticancer [14], as well as antiviral activities [15]. A promising study also suggested that Salvia lavandulifolia Vahl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up until now, different Salvia species have been investigated for their biological activity including anti-inflammatory [12], antioxidant-antifungal [13], anticancer [14], as well as antiviral activities [15]. A promising study also suggested that Salvia lavandulifolia Vahl.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rosmarinic acid derivatives from S. officinalis showed potent antioxidant activity greater than a standard synthetic antioxidant, trolox [27]. Moreover, S. fruticosa , which is rich in luteolin and rutin, showed significant anti-inflammatory activity comparable to a standard drug [12]. Therefore, it is interesting to discover the constituents and biological activities of different Salvia species due to their pharmacological potential.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to literature, it was found that, all the observed spectral data are similar to those reported for dehydro-abietic acid. 20,21 Also, it is isolated for the first time from Salvia fruticosa libanotica ( Figure 1 and Table 2). …”
Section: Extraction and Isolationmentioning
confidence: 96%
“…Different plant extracts demonstrated strong radical scavenging activity, whereas the ethyl acetate extract had the highest value in the roots and the lowest in the aerial parts. This antioxidant activity was correlated with the total phenolic content of different extracts, where rutin and luteolin were the most abundant constituents [22].…”
Section: Sage Extractsmentioning
confidence: 97%